2018
DOI: 10.1089/dia.2017.0198
|View full text |Cite
|
Sign up to set email alerts
|

Using Mobile Health to Improve Social Support for Low-Income Latino Patients with Diabetes: A Mixed-Methods Analysis of the Feasibility Trial of TExT-MED + FANS

Abstract: mHealth is a feasible, acceptable, and promising avenue to improve social support and diabetes outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 44 publications
0
83
0
1
Order By: Relevance
“…The Alive-PD intervention promoted social support by creating virtual teams using a participant messaging system and the option to share content on social media [21]. Gamification methods include healthyliving challenges [22,31], team competitions, a points system with monetary rewards [21], trivia questions [22] and quizzes [21,27]. Engagement may also be promoted with enhanced media, including video messages [27,32] and voice recognition [33].…”
Section: Patient Engagementmentioning
confidence: 99%
“…The Alive-PD intervention promoted social support by creating virtual teams using a participant messaging system and the option to share content on social media [21]. Gamification methods include healthyliving challenges [22,31], team competitions, a points system with monetary rewards [21], trivia questions [22] and quizzes [21,27]. Engagement may also be promoted with enhanced media, including video messages [27,32] and voice recognition [33].…”
Section: Patient Engagementmentioning
confidence: 99%
“…Beneficial effects of technology use on self-management and health outcomes were typically reported in studies that addressed non-professional social support by the patient's personal networks [37,38]. The use of social media, online communities, or mobile health (mHealth) has enhanced or improved psychological empowerment [39,40], self-care information and knowledge [38,41], blood glucose levels (HbA1c), as well as glucose self-monitoring and physical activity [3,42], and other health aspects [43][44][45]. The inclusion of family members or spouses in technological diabetes management systems was found to improve their understanding of self-management requirements and affected the communication about diabetes and the support of the patient positively [46].…”
Section: Social Support and Technology-supported Diabetes Selfmanagementmentioning
confidence: 99%
“…The patients with cardiometabolic disease studied reported that lifestyle-targeting text messaging approaches were feasible and acceptable, and that the text messages were easy to understand (88%) and were sent at an Connected Health Interventions to Cardiovascular Disease Prevention Agher et al 549 appropriate frequency (71%), in appropriate language (88%). Most of the studies used "smartphone health applications (connect)" [8][9][10][11][12]15,16,19,20,22,[24][25][26][27] . "Focus group" (do) and "Education" (read) were used together in two articles.…”
Section: Connected Health Interventionmentioning
confidence: 99%